2011
DOI: 10.1371/journal.pone.0026060
|View full text |Cite
|
Sign up to set email alerts
|

R1507, an Anti-Insulin-Like Growth Factor-1 Receptor (IGF-1R) Antibody, and EWS/FLI-1 siRNA in Ewing's Sarcoma: Convergence at the IGF/IGFR/Akt Axis

Abstract: A subset of patients with Ewing's sarcoma responds to anti-insulin-like growth factor-1 receptor (IGF-1R) antibodies. Mechanisms of sensitivity and resistance are unknown. We investigated whether an anti-IGF-1R antibody acts via a pathway that could also be suppressed by small interfering (si) RNA against the EWS/FLI-1 fusion protein, the hallmark of Ewing's sarcoma. The growth of two Ewing's sarcoma cell lines (TC-32 and TC-71) was inhibited by the fully human anti-IGF-1R antibody, R1507 (clonogenic and MTT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Under certain conditions, miRNAs can switch from their repression to activation function through upregulating their targets (Vasudevan et al, 2007), such as let-7a. Lu et al (2007Lu et al ( , 2011 found that ectopic let-7a expression significantly activated the expression of insulin-like growth factor (IGF)-II, which was reported to play an important role in the tumor progression of ES (Zhan et al, 1995), and some clinical trials that target IGF/IGF-1R/Akt axis are under investigation for future ES treatments (Huang et al, 2011). Thus, these conflicting reports promote us to explore the exact function and relative molecular mechanisms of let-7a in ES.…”
mentioning
confidence: 99%
“…Under certain conditions, miRNAs can switch from their repression to activation function through upregulating their targets (Vasudevan et al, 2007), such as let-7a. Lu et al (2007Lu et al ( , 2011 found that ectopic let-7a expression significantly activated the expression of insulin-like growth factor (IGF)-II, which was reported to play an important role in the tumor progression of ES (Zhan et al, 1995), and some clinical trials that target IGF/IGF-1R/Akt axis are under investigation for future ES treatments (Huang et al, 2011). Thus, these conflicting reports promote us to explore the exact function and relative molecular mechanisms of let-7a in ES.…”
mentioning
confidence: 99%
“…Figure 2C shows that, in the ES cell line TC71, drug treatment was able to markedly reduce IGF1R phosphorylation at Y1135/Y1136, two major autophosphorylation sites in the receptor activation loop [20]. TC71 cells carry the prototypical EWS-FLI1 fusion and, consistently with a common pattern of IGF/IGF1R axis deregulation, express high levels of IGF1R and of both IGF1 and IGF2 likely involved in autocrine loops [21]. Nonetheless, IGF1R remains highly responsive to exogenous IGF2 in TC71 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IGF-1R antibodies were recently reported to have single agent activity in recurrent ovarian cancer and relapsed thymoma, although thymoma treatment was associated with the development of autoimmune conditions including red cell aplasia [45,46]. Activity in EWS and childhood sarcomas may be a consequence of functional interactions between oncogenic fusion proteins (EWS-FLI1 and related fusion partners) and the IGF pathway [4750]. …”
Section: Clinical Trials: Reality Checkmentioning
confidence: 99%